Compressor of femtosecond laser pulses based on supercritical xenon. (July 2018) - Didenko, N.V.; Konyashchenko, A.V.; Losev, L.L.; Pazyuk, V.S.
Abstract: A time compressor of femtosecond laser pulses is developed using supercritical xenon as an active medium. Laser pulses with a duration of 300-fs and an energy of 8 μJ are compressed to 23 fs with an efficiency of 40 %.